RELATIONSHIP BETWEEN VON WILLEBRAND FACTOR DEGRADATION AND HEYDE SYNDROME DIAGNOSIS - Flavio Gomes Jardim Filho, Marcelo (Health and Society, 2024)
Heyde’s Syndrome is a clinical condition characterized by the coexistence of aortic stenosis and gastrointestinal bleeding, typically associated with angiodysplasia. This study reviews recent literature, highlighting the relationship between aortic stenosis and the degradation of von Willebrand factor (vWF), leading to the development of acquired von Willebrand disease (AVWD). The review addresses the key biochemical parameters and diagnostic methods used for identifying the syndrome, emphasizing the importance of echocardiography for detecting aortic stenosis and multimer analysis of vWF for confirming AVWD. The analysis includes discussions on the diagnostic challenges and clinical implications of the syndrome, proposing guidelines that could improve therapeutic management and reduce associated morbidity. It concludes that an integrated, evidence-based diagnostic approach is essential for the early detection and effective treatment of Heyde’s Syndrome.